Future of biomedical, agricultural, and biological systems research using domesticated animals. Issue 4 (29th January 2022) - Spencer, Thomas E; Wells, Kevin D; Lee, Kiho; Telugu, Bhanu P; Hansen, Peter J; Bartol, Frank F; Blomberg, LeAnn; Schook, Lawrence B; Dawson, Harry; Lunney, Joan K; Driver, John P; Davis, Teresa A; et al.
Abstract: Increased knowledge of reproduction and health of domesticated animals is integral to sustain and improve global competitiveness of U.S. animal agriculture, understand and resolve complex animal and human diseases, and advance fundamental research in sciences that are critical to understanding mechanisms of action and identifying future targets for interventions. Historically, federal and state budgets have dwindled and funding for the United States Department of Agriculture (USDA) National Institute of Food and Agriculture (NIFA) competitive grants programs remained relatively stagnant from 1985 through 2010. This shortage in critical financial support for basic and applied research, coupled with the underappreciated knowledge of the utility of non-rodent species for biomedical research, hindered funding opportunities for research involving livestock and limited improvements in both animal agriculture and animal and human health. In 2010, the National Institutes of Health and USDA NIFA established an interagency partnership to promote the use of agriculturally important animal species in basic and translational research relevant to both biomedicine and agriculture. This interagency program supported 61 grants totaling over $107 million with 23 awards to new or early-stage investigators. This article will review the success of the 9-year Dual Purpose effort and highlight opportunities for utilizing domesticated agricultural animals in research. Abstract : Increased knowledge of reproduction and health of domesticated animals is integral to sustain and improve global competitiveness of U.S. animal agriculture, understand and resolve complex animal and human diseases, and advance fundamental research in sciences that are critical to understanding mechanisms of action and identifying future targets for interventions.